Determinants of online waqf acceptance among academicians / Mohamad Syafiq Abdullah - Abdullah, Mohamad Syafiq (2017)
Online waqf also known as e-donation is one of the creative means for people to perform charitable activity. This paper aimed to investigate the relationship between four determinant factors (perceived usefulness, perceived ease of use, perceived religiosity and amount of information) and online waqf acceptance among academicians. The respondents were 40 lecturers of UiTM Johor and 60 teachers of SMK Bukit Merchu Kuala Kangsar, Perak. They were asked to answer a set of questionnaire. The respondents were selected by using convenience sampling since the requirements of this research is quite strict which are the academicians must have at least one Islamic bank account and have at least one year experience of using internet banking facility. The data obtained were analysed by using IBM SPSS Statistics 22.0 version. This study were using descriptive analysis, test of goodness of data, correlation analysis and regression analysis. Results of this current study found that there is significant relationship between perceived usefulness and perceived religiosity; and online waqf acceptance.